DETORQUEO, QUIRKY, and ZERZAUST represent novel components involved in organ development mediated by the receptor-like kinase STRUBBELIG in Arabidopsis thaliana - Fulton, Lynette; Lohmann, Jan U. (PLoS Genetics, 2009)
Author Summary: Plant organs, such as flowers or leaves, are made up of distinct cell layers. Although communication across these cell layers is essential for organ development, we have only recently gained some insight into the underlying mechanisms. Receptor-like kinases are cell-surface receptors that perceive and relay intercellular information. In Arabidopsis, the receptor-like kinase STRUBBELIG is required for inter-cell-layer communication during floral development, amongst other functions; little is known, however, concerning its exact signaling mechanism. Here, we identified three new genes called DETORQUEO, QUIRKY, and ZERZAUST. Plants defective in any of these genes strongly resemble the strubbelig mutant, both at the whole-organ and cellular levels. Thus, all four genes may share or contribute to a common signaling pathway essential for plant morphogenesis. Analyses revealed complex interactions between the genes, indicating that each has additional and distinct activities. We provide the molecular nature of QUIRKY; the encoded protein is likely membrane-localised and predicted to require Ca2+ for activity. In light of analogous animal models, we speculate that QUIRKY facilitates transport of molecules to the cell boundary and may support a STRUBBELIG-related extracellular signal. These results open new inroads into a molecular understanding of inter-cellular communication during flower development.